2014
DOI: 10.1179/1743132813y.0000000289
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dopamine transporter expression in the midbrain following traumatic brain injury: an immunohistochemical andin situhybridization study in a mouse model

Abstract: These findings indicated that TBI induced changes in DAT expression in the RRF. Because the DAT pumps dopamine (DA) out of the synapse back into the cytosol and maintains DA homeostasis, the decreased expression of DAT after TBI may result in decreased DA neurotransmission in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
5
20
0
Order By: Relevance
“…A variety of studies had reported that reduced extracellular dopamine levels may result in depressionlike behavior. Nevertheless, none has reported the delayed effect of the dopaminergic level as revealed by our data [48][49][50]. Interestingly, amantadine treatment demonstrated an intense effect on behavioral modification after the acute phase (3 days) of surgery [ Fig.…”
Section: Discussionmentioning
confidence: 51%
“…A variety of studies had reported that reduced extracellular dopamine levels may result in depressionlike behavior. Nevertheless, none has reported the delayed effect of the dopaminergic level as revealed by our data [48][49][50]. Interestingly, amantadine treatment demonstrated an intense effect on behavioral modification after the acute phase (3 days) of surgery [ Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Dysfunctional DAergic signaling may explain many of the persistent cognitive deficits observed with TBI (see review, Bales et al 10 ). Decreased DA transporter (DAT) levels in the prefrontal cortex and striatum 11 have been confirmed in a rat model after TBI 12 , suggesting compensatory action by DA neurons to increase DA signaling post-TBI. In severe levels of injury associated with the controlled cortical impact (CCI) model of experimental TBI, tyrosine hydroxylase (TH), a rate-limiting enzyme in the synthesis of DA is upregulated in presynaptic terminals in the frontal cortex 13 and in the striatum 10,14 .…”
Section: Introductionmentioning
confidence: 97%
“…Because DAT plays an important role in maintenance of DA homeostasis, the decreased expression of DAT after TBI may also result in altered DA neurotransmission in the brain. 72 TBI-induced DA neurotransmission deficits were also attributable to deficits in TH activity. TBI reduces striatal TH activity and potassium-evoked DA release in rats at 1 wk after injury.…”
Section: Secondary Insults After Tbi (Related To Dopamine Suppression)mentioning
confidence: 96%
“…DAT plays an important role in recycling DA (DA) from the synapse and maintaining DA homeostasis, so the decreased expression of DAT after TBI may result in altered DA neurotransmission in the brain. 72 Neural plasticity and neurogenesis effects of environmental enrichment (EE) in neurodegenerative diseases like PD have been studied. 95,96 The restoration of monoamine (DA and serotonin) transporter function after EE has also been documented.…”
Section: Secondary Insults Related To the Dopamine Systemmentioning
confidence: 99%